The beginning of the Technological Pedagogical Content Knowledge in assistant student to the university. Study of cases - Moreyra, Mara (2019)
This work aims to understand the processes of Construction of the Technological Didactic Knowledge of the Content in beginner university affiliates, considering them as teachers in training, in the context of the National University of the Northeast, Argentina. Taking into account the university context, we seek to deepen and broaden the analysis of three cases from different careers of the faculties of said university: Faculty of Medicine, Exact and Natural Sciences and Surveying and Humanities; whose careers and subjects are: Medicine (Biochemistry), Faculty of Biology (Biology of the Ropes) and Bachelor of Science in Education (Project Development and Evaluation). Given the type of analysis we seek, we frame this research within the interpretive paradigm and qualitative approach. Likewise, the methodology adopted was the case study, whose information collection instruments were successive in-depth interviews, individual semi-structured; Observations of their ascription practices, curricular materials and projects of ascription of the subjects. Regarding the conclusions, we point to university ascription as a complex vocational training field, enriched with knowledge and experiences that allow the deployment of a series of initial skills in beginners, which are grouped into conventional and emerging skills.